Thermal stiffening of hydrophobic association hydrogels. (6th June 2018) - Owusu-Nkwantabisah, Silas; Gillmor, Jeffrey; Bennett, Grace; Slater, Gary; Szakasits, Megan; Rajeswaran, Manju; Antalek, Brian
Abstract: Strong and tough hydrogels, important for several materials and bio-applications, typically consist of nanocomposites and double networks. There is the need to create hydrogels that exhibit tunable mechanical properties on demand without compromising other functional properties. This work demonstrates the rapid thermal stiffening of a hydrophobic association hydrogel while maintaining its optical quality and chemical composition. Up to 100-fold increase in modulus of the methacrylate-based hydrogel was achieved by an increase in temperature from 25 °C to 50 °C. Based on various characterizations, we proposed that the thermal stiffening is related to the polymer conformational changes and the ensuing increase in inter-chain hydrophobic associations at the expense of intra-chain associations. The temperature above which thermal stiffening occurs can be tuned with the polymer content in the hydrogel. Furthermore, hydrogels containing a lower mole fraction of the hydrophobic groups exhibit unusual "gel-sol-gel" transitions with temperature increase. Graphical abstract: Image 1 Highlights: Hydrophobic association hydrogels portrayed tunable mechanical properties based on temperature The thermal stiffening does not compromise optical properties and chemical composition of the hydrogel. The thermal stiffening entailed a "stiff-soft-stiff" transition as temperature increased from 5 to 50 °C. The thermal stiffening showed dependence on the extent of hydrophobic associations. Up to 100-fold increase in modulus of hydrogel was recorded for a temperature increase from 25 to 50 °C.